Transmedia narratives in communication in times of crisis: the 2016 Ecuador earthquake - Arrobo-Agila, Juan Pablo (2021)
The research focuses on analyzing transmedia narratives when reporting on an earthquake from a national digital newspaper, an international one, and also the impact of Facebook when disseminating the event. The objective is to compare the content generated about the earthquake of April 16, 2016, in Ecuador through transmedia tools in El Comercio (Ecuador) and El País (Spain), and Facebook. The aim is to know the role of the audience as prosumers of information. The methodology applied was mixed: qualitative and quantitative; the sample analyzed was 1126 informative pieces from El Comercio, 44 from El País and 1155 Facebook mentions. The need to educate and inform citizens about preventing the consequences of natural disasters and the treatment given by digital media justifies the study. The importance of having prevention measures makes this research a contribution to citizenship. The journalistic narrative is strengthened by various resources that allow portraying a story in different contexts; as shown in this research, the most used resources are still photography and video